INSTALLATION CHARACTER VALUES OF DISCIPLINE AND RESPONSIBILITY IN SANTRI THROUGH THE RO'AN TRADITION AT MIFTAHUL HUDA SIWATU ISLAMIC BOARDING SCHOOL - latifah; Faisal Kamal; Fatiatun (Alphateach (Jurnal Profesi Kependidikan dan Keguruan), 2025)
This investigation aims to: 1) To find out the concept of instilling the character values ​​of discipline and responsibility of students through the ro'an tradition at the Miftahul Huda D1 Siwatu Islamic Boarding School, 2) to find out the instillation of the character values ​​of discipline of students through the ro'an tradition at the Miftahul Huda D1 Siwatu Islamic Boarding School, and 3) to find out the instillation of the character values ​​of responsibility of students through the ro'an tradition at the Miftahul Huda D1 Siwatu Islamic Boarding School. This thesis uses a qualitative research approach with a field research approach. Data collection techniques include observation, interviews, and documentation. Data sources are obtained from the caretakers, administrators, santri, and alumni of the Miftahul Huda D1 Islamic Boarding School. The analysis technique used is an inductive method, which is an analysis based on the data obtained, then developing a specific relationship pattern or hypothesis. The analysis used is an analysis before and during the fieldwork. The results of the study show that: (1) The concept of instilling the character values ​​of discipline and responsibility through the ro'an tradition includes habituation, observing and imitating figures who are considered influential by the students, and receiving information verbally. This ro'an activity is carried out every Sunday morning. This series of activities includes gathering students in the yard of the pondok, distributing tasks and taking attendance. (2) Instilling the character values ​​of discipline through this ro'an tradition uses the exemplary method, habituation method, advice method, supervision method, and rule enforcement method. (3) Instilling the character values ​​of responsibility through this ro'an tradition uses the habituation method, giving tasks, supervision, rule enforcement, and cooperation